Green insurance, technology insurance, and corporate green innovation - Pu, Chengyi; Mo, Chou; Li, Peihuan (Frontiers in Environmental Economics, 2024)
The “dual-carbon” strategy was first written into China's “Government Work Report” in 2021, bringing green low-carbon development and green innovation to an unprecedented height. At the financial policy level, the Chinese government actively promotes the development of a green financial system represented by green bonds, green insurance, science and technology insurance, and green credit. Existing literature studies on green insurance and science and technology insurance mainly focus on the relevant legal system, the impact on corporate and risk management system, insurance types and service models, subsidy policies, and the problems and challenges they face. However, existing studies have studied the impact of green insurance and science and technology insurance on corporate' green innovation. In particular, the impact of their interaction on corporate' green innovation is rarely mentioned. From the perspective of green insurance and science and technology insurance to promote corporate' green innovation, based on the data sample of Shanghai and Shenzhen A-share listed companies from 2014 to 2015, this paper comprehensively investigated and analyzed the impact of green insurance and science and technology insurance on corporate' green innovation, and analyzed the interaction effect of the two. The research perspective of enterprise green innovation is expanded. The analysis conclusion of this paper provides new ideas and empirical evidence for Chinese corporate to realize faster and more efficient green transformation, which is conducive to stimulating the vitality of enterprise green innovation and development.